2021
DOI: 10.1093/ofid/ofab636
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Testing and Linkage to Care Among Adults on Probation in a Large US City

Abstract: Background Despite constituting the largest segment of the correctional population, individuals on probation remain largely unstudied with respect to hepatitis C virus (HCV) testing and linkage-to-care. We implemented an HCV testing and patient navigation program at an adult probation department. Methods Adults were tested at a local probation department with a rapid point-of-care HCV antibody (Ab) assay followed by a lab-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…Our results align with other studies which have shown a higher prevalence among adults on probation compared to the general population (Hawks et al, 2020;Zaller et al, 2016). We recently published results of a prospective HCV testing and linkage to care program located on-site at the same probation department of this retrospective analysis (Kamis et al, 2022). In that study, 13% (56/417) of individuals tested anti-HCV positive, and of the 34 individuals who were found to have detectable HCV RNA, 14 (41%) linked to care and 1 (3%) achieved cure.…”
Section: Data Reported To the Colorado Department Of Publicsupporting
confidence: 91%
See 2 more Smart Citations
“…Our results align with other studies which have shown a higher prevalence among adults on probation compared to the general population (Hawks et al, 2020;Zaller et al, 2016). We recently published results of a prospective HCV testing and linkage to care program located on-site at the same probation department of this retrospective analysis (Kamis et al, 2022). In that study, 13% (56/417) of individuals tested anti-HCV positive, and of the 34 individuals who were found to have detectable HCV RNA, 14 (41%) linked to care and 1 (3%) achieved cure.…”
Section: Data Reported To the Colorado Department Of Publicsupporting
confidence: 91%
“…Some studies have assessed HCV prevalence among this population, including a study that found 9% (12/130) HCV antibody positivity among a group of individuals on probation or parole in Rhode Island (Zaller et al, 2016) and a national survey that found a nearly five-fold higher adjusted odds ratio of having hepatitis C or hepatitis B among probationers compared to the general population (Hawks et al, 2020). Our group conducted a study of HCV testing located on-site at a probation department where we found a 13% HCV antibody positivity among the 417 individuals tested (Kamis et al, 2022).…”
Section: Open Accessmentioning
confidence: 77%
See 1 more Smart Citation
“…High attrition was also observed in Denver, Colorado; among 52 participants testing hepatitis C antibody positive using onsite point of care tests with reflex to offsite RNA testing using the same blood sample, 34 (65%) had detectable hepatitis C RNA, of which 14 (27%) were linked to a treatment provider, and only four (8%) completed treatment. 26 …”
Section: Hepatitis Care In Community Corrections: a Novel Settingmentioning
confidence: 99%
“…However, unlike HCV, many HIV testing programs have successfully implemented active linkage programs, yielding successful linkage rates of well over 80% within 3 months of HIV diagnosis [13]. Linkage navigators have been utilized in community-based HCV testing programs, but while the role of navigation has been described in these settings, the added benefit of a linkage navigator above and beyond standard clinician referral has not been evaluated in a prospective, comparative manner [14][15][16]. Additionally, the effectiveness of navigators for people who inject drugs (PWID), a traditionally under-treated population, has not been assessed.…”
Section: Introductionmentioning
confidence: 99%